Challenges for biodiversity research in Europe - De Meester, L; Van Tienderen, P; Werger, M; Hector, A; Wörheide, G; Niemelä, J; Aguilar, A; Smets, E; Godfray, C; Sutherland, W; Bauhus, J; Courchamp, F; et al. (2011)
In 2010, the international year of biodiversity, new policies for preserving biodiversity in Europe and worldwide will be developed as targets set by older policies, such as to halt biodiversity loss in the EU by 2010, were not met. This paper aims at sharing the expertise LERU's members harbour to set the right priorities for new biodiversity policies. Three key observations point to the urgency of an effective biodiversity conservation policy: 1) the alarming global decline in biodiversity; 2) the associated diminishing return in ecosystem services that are key to human well-being; 3) the dangerous mix of climate change and biodiversity loss. There are important gaps in our knowledge of the regulating mechanisms of biodiversity and the relationship of biodiversity to ecosystem services. We therefore list 18 research challenges, which we consider to be the 'need-to-know' building blocks for a future research agenda. Filling the knowledge gaps is crucial to develop an efficient and sustainable policy towards biodiversity conservation. The research challenges are broadly grouped in five areas. A first set focuses on different challenges posed by documenting and monitoring biodiversity. A second group describes six research challenges on drivers of biodiversity that need more attention. These challenges relate to 1) insight into the processes of community assembly; 2) large and complex ecosystems; 3) landscape metapopulation structure; 4) ecoevolutionary dynamics; 5) species networks and identifying its key players; and 6) issues associated with complex dynamics and alternative stable states. The challenges of linking biodiversity, functional diversity, and ecosystem functioning and services are set out in a third group of research challenges, which also highlights the need to analyse ecosystem services at landscape level and to investigate the economics of biodiversity and ecosystem services. A fourth set of research challenges focuses on understanding how species respond to anthropogenic impact (global change), and a fifth group emphasizes the need to understand how species respond to nature conservation measures. Besides describing important research challenges, LERU also provides recommendations for effective biodiversity conservation strategies, which are not only aimed at policy makers, but also at researchers, other stakeholders and the general public: It is necessary to invest in a European infrastructure for biodiversity data and research. LERU emphasizes the importance for Europe to invest in adequate infrastructures which support biodiversity research to increase our knowledge on biodiversity and its impact on the functioning of ecosystems, and hence help decision makers in devising cost-effective management plans to reach the stated goals. There is a need for a powerful research agenda enhancing fundamental knowledge on biodiversity drivers and threats. This vigorous biodiversity-targeted research programme should be initiated at the European level, but also with strong national support. There is a great need for an effective translation of scientific knowledge into biodiversity practice to guarantee that scientific evidence is available to inform both policy development and practical implementation of conservation management. There is a need for a consistent and global biodiversity conservation policy, which also aims at changing the way people live and work in Europe to ensure biodiversity conservation within and outside Europe's borders. Given that biodiversity and ecosystem services are of paramount importance to the development of human societies in the long run, a "biodiversity check" in all policies should be implemented. When future biodiversity conservation strategies are developed, it should be verified if the measures taken are climate change-proof. The economic consequences of biodiversity loss and gain need to be quantified to enable a system in which the agent causing the loss will need to pay for the costs linked to the loss and the restoration of ecosystems, instead of society as a whole. Prevention is by far the most efficient strategy to reduce the number of invasive exotic species and their negative impact on biodiversity. To realise efficient prevention, a European strategy to deal with invasive exotic species is mandatory. LERU emphasizes the importance of collaboration across scientific disciplines for modern biodiversity research and therefore emphasizes the need for support for multidisciplinary collaborative networks. LERU calls for an improved science-policy interface in biodiversity protection, which could be realised by reinforcing the existing Intergovernmental platform on Biodiversity and Ecosystem Services (IPBES). Increased efforts for raising biodiversity education and awareness are necessary to get the neededsupport from society as a whole for a successful biodiversity policy. Research-intensive universities can play a leading role in this. Research-intensive universities can contribute to fighting biodiversity loss by implementing an ambitious biodiversity research agenda, by developing inter-university networks sharing research infrastructures, and by investing in biodiversity education. LERU considers the study of biodiversity and the ecological responses to environmental change a top priority with an enormous added value to society © 2010 Published by LERU.